Replica symmetry breaking in 1D Rayleigh scattering system: theory and validations - Qi, Yifei; Ni, Longqun; Ye, Zhenyu; Zhang, Jiaojiao; Bao, Xingyu; Wang, Pan; Rao, Yunjiang; Raposo, Ernesto P.; Gomes, Anderson S. L.; Wang, Zinan (Light, science & applications, 2024)
Spin glass theory, as a paradigm for describing disordered magnetic systems, constitutes a prominent subject of study within statistical physics. Replica symmetry breaking (RSB), as one of the pivotal concepts for the understanding of spin glass theory, means that under identical conditions, disordered systems can yield distinct states with nontrivial correlations. Random fiber laser (RFL) based on Rayleigh scattering (RS) is a complex disordered system, owing to the disorder and stochasticity of RS. In this work, for the first time, a precise theoretical model is elaborated for studying the photonic phase transition via the platform of RS-based RFL, in which we clearly reveal that, apart from the pump power, the photon phase variation in RFL is also an analogy to the temperature term in spin-glass phase transition, leading to a novel insight into the intrinsic mechanisms of photonic phase transition. In addition, based on this model and real-time high-fidelity detection spectral evolution, we theoretically predict and experimentally observe the mode-asymmetric characteristics of photonic phase transition in RS-based RFL. This finding contributes to a deeper understanding of the photonic RSB regime and the dynamics of RS-based RFL. This work reveals intrinsic mechanisms of photonic phase transitions with a precise theoretical model in 1D Rayleigh scattering system, and could have broad and profound impacts across various complex systems.